Determinan Ketepatanwaktu Pelaporan Keuangan Pada Organisasi Perangkat Daerah Dengan Sistem Pengendalian Intern Sebagai Pemoderasi - Hidni, Baiq Muslihan; Santoso, Budi; Pituringsih, Endar (E-Jurnal Akuntansi, 2021)
This study aims to analyze the effect of organizational commitment, leadership style and SAKD on the timeliness of financial reporting with the internal control system as a moderating variable. The research population is the accounting staff at 38 OPDs of West Nusa Tenggara Province. The results show that organizational commitment has a positive and significant effect on the timeliness of financial reporting. Leadership style and SAKD have a positive and insignificant effect on the timeliness of financial reporting. While the internal control system is not able to strengthen the influence of organizational commitment, leadership style, and SAKD on the timeliness of financial reporting. Keywords : Timeliness of Financial Reporting; Organizational Commitment; Leadership Style; SAKD; Internal Control System.